2003
DOI: 10.1124/jpet.102.042283
|View full text |Cite
|
Sign up to set email alerts
|

M1Receptor-Mediated Nitric Oxide-Dependent Relaxation Unmasked in Stomach Fundus from M3Receptor Knockout Mice

Abstract: Muscarinic receptors can mediate both contractile and relaxant responses in smooth muscle. The stomach fundus from wildtype mice possesses a neuronal M 1 receptor that mediates relaxation to carbamylcholine and (4-hydroxy-2-butynyl)-1-trimethylammonium-3-chlorocarbanilate chloride but is masked by M 3 receptor-mediated contraction to both agonists. When the M 3 receptor was deleted, cholinergic-induced relaxation was unmasked. M 1 receptor antagonism with pirenzepine, nitric oxide (NO) synthase inhibition wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…This result indicates that activation of muscarinic receptors is involved in the inhibitory response. A number of previous reports have examined this point; a relationship between the activation of muscarinic receptors and the relaxation has been reported in the rat jejunum [33] and the mouse fundus [36]. However, further study is necessary to clarify how the muscarinic receptor regulates the sustained relaxation.…”
Section: Discussionmentioning
confidence: 91%
“…This result indicates that activation of muscarinic receptors is involved in the inhibitory response. A number of previous reports have examined this point; a relationship between the activation of muscarinic receptors and the relaxation has been reported in the rat jejunum [33] and the mouse fundus [36]. However, further study is necessary to clarify how the muscarinic receptor regulates the sustained relaxation.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that the ability of the nitrergic neurotransmitter to induce relaxation of the rat gastric fundus was influenced by the mechanism used to induce tone, and sarcoplasmic/endoplasmic reticulum Ca 2ϩ ATPase appeared to play a role in nitrergic relaxation . From studies using wild-type and M 3 muscarinic receptor knockout mice, Stengel and Cohen (2003) …”
Section: B Stomachmentioning
confidence: 99%
“…Furthermore, it was recently suggested that a muscarinic receptor other than M 1 or M 3 stimulates NO synthase in the guinea pig gastric fundus [10] . In M 3 knockout mice, evidence was found for M 1 receptor-mediated gastric fundus relaxation [18] . It is also generally known that vagal motor pathways to the stomach consist of parallel inhibitory and excitatory cholinergic pathways that activate separate myenteric neurons via nicotinic receptors [3] .…”
Section: In Vitro: Basal Intragastric Tone and Evs-inducedmentioning
confidence: 99%